Kelayakan LKPD Berorientasi Assessment For Learning (Afl) Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Materi Larutan Penyangga - Gita Theresa Ary Sudarsono; Muchlis (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2023)
This study aims to determine the feasibility of student worksheets to improve learning outcomes in buffer solutions. LKPD feasibility in terms of validity, practicality, and effectiveness. This development research uses the Borg and Gall model. Validity data was obtained from the validator's assessment using a validation questionnaire. Practicality data is obtained based on the responses and activities of students. Effectiveness data was obtained from the pretest-posttest N-gain test. The results showed that all validity items obtained an average percentage of 84.5% with valid criteria. Student response to LKPD was 88.9% -100% in very good category. Relevant activities of students at meetings 1 and 2 respectively were 88.9% and 94.5%. Based on the responses and activities of the students, the LKPD that was developed was included in the practical category. The effectiveness data shows that the overall N-gain in the high and medium categories is 100%, this indicates that the LKPD is said to be effective. Based on the validity, practicality and effectiveness of assessment-oriented worksheets for learning, they are effective in improving learning outcomes in buffer solutions.